Features of main band parameters for crystalline modification of Cd₃As₂ without center of symmetry - Chuiko, G.P.; Dvornik, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The so-called loops of extremes exist for the modification of Cd₂As₂ without the center of symmetry. The maximal spin splitting of bands is observable along a direction normal to the main crystalline axis. The number of topological transitions is increased for the surfaces of equal energy in all valence bands. The energies of the extremes of bands and topological transitions are calculated within the generalized Kane’s and Kildal-Bodnar’s model for a modification without the center of symmetry. It was established from the indirect solutions of the dispersion equation k(ε) that the functions of the density of states near to the bottom of the conduction band change differently for different spin subbands with variation in energy. A similar situation is observed for the effective masses which demonstrate a nonlinear dependence on energy with a minimum caused by the degeneration of energy bands.